Predictors of intimate partner violence and associated marital disruption among ever-married women in sub-Saharan Africa: a multi-country analysis for policy and intervention priorities - Ani, Judith Ifunanya; Katende-Kyenda, Lucky Norah (Frontiers in Sociology, 2025)
IntroductionIntimate Partner Violence (IPV) remains a significant public health and human rights concern globally, disproportionately affecting women. This study investigates predictors of IPV and its association with marital disruption among ever-married women in sub-Saharan Africa.MethodsCross-sectional data from the Demographic and Health Surveys (DHS) covering 25 sub-Saharan African countries was analysed. The study examined the prevalence of IPV and marital disruption, focusing on socio-demographic characteristics (age, residence, education, and union duration) and partner-related factors (controlling behavior, alcohol use, age differences, and exposure to parental violence).ResultsFindings revealed a high prevalence of IPV across the study population. IPV was significantly associated with marital disruption, particularly among women aged 25–29, those residing in rural areas, with primary education, and those in unions lasting 5–9 years. Partner characteristics, including controlling behavior, alcohol consumption, larger age gaps, and a history of witnessing parental violence, were strongly linked to both IPV and increased risk of separation or divorce. Women who experienced any form of IPV had 56% lower odds of remaining in a current union, highlighting IPV as a major driver of marital instability.DiscussionThese results underscore the urgent need for targeted, context-specific interventions to address IPV and mitigate its destabilizing effects on family structures. Policy recommendations include advancing women’s education and economic empowerment, promoting community-level awareness campaigns, and transforming harmful gender norms. Such interventions are critical for achieving Sustainable Development Goal 5 on gender equality and ensuring women’s safety and stability in intimate relationships.